Introduction of a Management Toolkit for Lewy Body Dementia: A Pilot Cluster‐Randomized Trial. Issue 1 (22nd September 2020) - O'Brien, John T.; McKeith, Ian G.; Thomas, Alan J.; Bamford, Claire; Vale, Luke; Hill, Sarah; Allan, Louise; Finch, Tracy; McNally, Richard; Hayes, Louise; Surendranathan, Ajenthan; Kane, Joseph P.M.; et al.
ABSTRACT: Background: Lewy body dementia, comprising both dementia with Lewy bodies and Parkinson's disease dementia, is challenging to manage because of a complex symptom profile and lack of clear evidence‐based management guidelines. Objectives: We assessed the feasibility of undertaking a cluster randomized study of the introduction of an evidence‐based management toolkit for Lewy body dementia, assessing the outcomes for patients and carers as secondary measures. Methods: We randomized 23 memory/dementia, movement disorder, or nonspecialist secondary care services to the management toolkit or usual care. People with dementia with Lewy bodies or Parkinson's disease dementia underwent assessments of cognition, motor and neuropsychiatric symptoms, and global outcome at baseline and 3 and 6 months. Healthcare, personal and social care costs, and carer‐related outcomes of carer stress, depression, and anxiety were also examined. Results: A total of 131 participants were recruited (target 120), for whom 6‐month data were available on 108 (83%). There was a benefit of being in the intervention arm for carers (reduced Zarit Burden Scale [ P < 0.01], reduced depressive symptoms [ P < 0.05]), who also reported less marked patient deterioration on the global outcome measure ( P < 0.05). There were no significant differences in other outcomes or in costs between groups. Conclusions: The introduction of an evidence‐based management toolkit for Lewy body dementia was feasible and associated with some benefits, especially for carers. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society